Inovasi Aplikasi Sistem Informasi Perizinan dan Investasi Kota Surabaya (Sipintar) Pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Surabaya - Rachel Amanda Delia; Galih Wahyu Pradana; Muhammad Farid Ma'ruf; Deby Febriyan Eprilianto (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Digital transformation in public services encourages governments to develop technology-based innovations to improve service quality and efficiency. One of these innovations is the Surabaya Licensing and Investment Information System Application (SIPINTAR), developed by the Investment and One-Stop Integrated Service Office of Surabaya City (DPMPTSP) as a chatbot-based information service for licensing and investment matters. This study aims to analyze the SIPINTAR innovation using Everett M. Rogers' Diffusion of Innovation theory, which consists of five attributes: relative advantage, compatibility, complexity, trialability, and observability. This research employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation involving informants selected using purposive sampling techniques. Data analysis was conducted using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings indicate that SIPINTAR has generally contributed positively to improving the quality of public services in licensing and investment. The application increases service efficiency, accelerates access to information, and reduces the workload of public officers. In addition, SIPINTAR is compatible with existing regulations and integrated with other service systems. However, several challenges remain, including limited public digital literacy, the system's dependence on specific keywords, and the low visibility of the application's benefits among non-users.